Electrochemically Exfoliated Porous WS2 Nanosheets: A Potential Electrochemical Sensing Platform for Chlorpromazine Detection. Issue 10 (1st January 2019) - Subramanian, Nandhini; Priya, Karuppiah Mohana; Valappil, Manila O.; Nesakumar, Noel; Kesavan, Srinivasan; Alwarappan, Subbiah
Abstract : In this work, tungsten disulfide (WS2 ) nanosheets were obtained from bulk WS2 by electrochemical exfoliation and employed for the development of novel, sensitive and selective sensor for the determination of chlorpromazine (CPZ). It is worth mentioning that for the first time a glassy carbon (GC) electrode modified with WS2 sheets is employed for the quantitative voltammetric determination of CPZ in human urine samples. A pair of well-defined reversible CPZ redox peaks (560 and 500 mV) is observed at WS2 modified GC electrode due to the high surface area and excellent electrocatalytic activity of WS2 sheets towards CPZ oxidation and reduction reaction. The GC/WS2 sheets modified electrode exhibited a low detection limit of 4 μM towards CPZ. Further, the sensitivity of the GC/WS2 sheets modified electrode is found to be 1.416 μA cm −2 mM −1 over a linear range of 0−0.69 mM. Finally, the application of as-fabricated electrode for determination of CPZ in human urine samples is demonstrated.